2012
DOI: 10.1002/micr.21945
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐free radial forearm flap for head and neck reconstruction in vessel‐depleted neck after radiotherapy or radical neck dissection

Abstract: The SF-RFF is a reliable and versatile procedure for facial, oral, or larynx reconstruction. This hybrid version of the radial forearm free flap is particularly appropriate when no suitable recipient veins are available as a result of radiation or prior surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…However in their study of 60 free flaps done after previous neck dissection, Head et al reported no cases of free flap failures . Quilichini et al used cephalic vein in vessel‐depleted neck after radiotherapy or radical neck dissection to achieve successfully in free tissue transfers for head and neck reconstruction . Consequently, the next question we seek to answer is whether free tissue transfer is safe in patients that had undergone both previous radiotherapy and neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…However in their study of 60 free flaps done after previous neck dissection, Head et al reported no cases of free flap failures . Quilichini et al used cephalic vein in vessel‐depleted neck after radiotherapy or radical neck dissection to achieve successfully in free tissue transfers for head and neck reconstruction . Consequently, the next question we seek to answer is whether free tissue transfer is safe in patients that had undergone both previous radiotherapy and neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The reliable pedicle length and predictability of harvest make the radial forearm free flap a commonly utilized reconstructive technique for cutaneous defects of the head and neck. In cases with vessel-depleted necks where veins are unavailable, a semifree radial forearm harvest has been described dissecting the cephalic vein proximally and performing a single arterial anastomosis, which is unique to this flap [23]. Donor site morbidity is well tolerated, however generally inferior to the anterior thigh flap [24, 25] (Figures 2, 3, and 4).…”
Section: Reconstructive Managementmentioning
confidence: 99%
“…In such situations, recipient vessels of the thoracoacromial or cephalic system can provide an alternative source of blood supply. However, vein grafts or vascular loops are necessary to provide a pedicle long enough for tensionless anastomosis (Urken et al, 2006;Ethunandan et al, 2007;Aycock et al, 2008;Quilichini et al, 2012;Roche et al, 2012;Karle et al, 2013), significantly increasing the risk for flap loss (Bozikov and Arnez, 2006). For these patients, we described a temporary perfusion of composite fibular flaps by anastomosing the flaps to the radial vessels ("carrier flap") with long-term fixation of the arm in an elevated position (Wolff et al, 2003(Wolff et al, , 2009.…”
Section: Introductionmentioning
confidence: 98%